Feminism, Class Consciousness and Household-Work Linkages Among Registered Nurses in Victoria - Carroll, William; Warburton, Rennie (Labour/Le Travailleur, 1989)
Abstract This survey of 179 Registered Nurses at a large acute care hospital deals with connections between the practices in which nurses are engaged in households and workplaces and the consciousness which both informs and arises from those practices. A large majority of respondents was opposed to male prerogatives and in favour of more domestic equality and removing pay inequities for women. On more controversial gender issues and with respect to class politics, respondents' opinions were diverse. Younger, more subordinate, better educated nurses and those with working class spouses and relatively egalitarian domestic arrangements manifested progressive attitudes on class and gender issues, but these statistical relationships were weak. The lack of clear-cut correspondence between social position and conscious-ness may reflect nurses' contradictory experiences in, for example, cross-class marriages and quasi-professional work situations.